MORPHOLOGICAL CHANGES DURING THE DEVELOPMENT OF SOMATIC EMBRYOS OF SAGO (Metroxylon sagu Rottb.) - Pauline D. Kasi; Sumaryono Sumaryono (Indonesian Agency for Agricultural Research and Development, 2007)
Development of somatic embryos of sago (Metroxylon sagu Rottb.) on agar-solidified medium are highly varied producing heterogeneous seedlings. Understanding of this phenomenon may help in improving the cultural procedures and conditions of sagosomatic embryogenesis to obtain uniform seedlings in a large scale. This experiment was conducted at the laboratory for plant cell culture and micropropagation, Indonesian Biotechnology Research Institute for Estate Crops from January to March 2006 to examine morphological changes i.e. color and development stages of sago during their somatic embryo development on an agar-solidified medium. Twenty single globular somatic embryos of sago with specific color (yellowish, greenish, and reddish) were cultured in a Petri dish supplemented with a solid medium. The medium was a micronutrients-modified MS (MMS) with half strength of macronutrients containing 0.01 mg l-1 ABA, 2 mg l-1 kinetin, 20 g l-1 sucrose, 0.5 g l-1 activated charcoal, and 2 g l-1 gelrite. Parameter observed was the percentage of embryo’s number based on color and developmental stage. The result showed that at the end of 6-week culture passage, most originally greenish (80.8%) and reddish (95.8%) embryos remained unchanged in their colors, whereas almost half of the originally yellowish embryos turned to greenish and only 30%remained yellowish. At the same time, single globular embryos have changed gradually into the next developmental stages, although not all of the embryos were germinated. The initial color of embryo affected the rate of the developmental stage changes. Yellowish and greenish globular embryos developed more rapidly into cotyledon or germinant stages at 58% and 55% respectively, in 6 weeks than the reddish ones (41%). Therefore, the yellowish and greenish embryos are the best sources of material for in vitro mass propagation and synthetic seed production of sago.